Reinforcing Strategy for Micro, Small, and Medium Enterprises (Msmes) Through The Twitter Account of The Ministry of Cooperatives and Smes and Using The Hashtag #UMKMBangkit in Indonesia - Fridayani, Helen Dian; Eko Atmojo, Muhammad; Chiang, Li-Chun (Universitas Pancasakti Tegal, 2023)
The global COVID-19 pandemic is a challenge, especially for the Indonesian government in various sectors, one of which is the MSME sector. Considering the MSMEs are one of the largest contributors to GDP in Indonesia, the government must seek to have an appropriate and effective MSME recovery strategy. One of them is the delivery of information related to COVID-19 using social media because this big pandemic also produces various information that can create tension for the community. Therefore, there is a need for effective and appropriate government communication to the community regarding the recovery of MSMEs. Hence, the purpose of this research is to look at the MSME recovery strategy through the @KemenKopUKM Twitter account with the dissemination of actual and valid information to support the development of MSMEs in Indonesia. This can be seen by knowing the intensity of government communication and seeing the relationship between government communication interactions through the Twitter account @KemenKopUKM. This study uses a qualitative research approach and data analysis is processed with the help of NVivo 12 Plus software. The data was obtained through the Twitter account @KemenKopUKM and saw the hashtag #UMKMBangkit. From the results of the study, it was found that the communication built by the government during the COVID-19 pandemic through the Twitter account @KemenKopUKM was active and effective in conveying information to the public related to the development of MSMEs during the pandemic, for example, marketing, how to get capital, digitalization workshops for MSMEs, and many more